13C-NMR Studies of Some Heterocyclically Substituted Chromones - Prabha Sharma, Vinay (Asian Journal of Chemistry, 2016)
Synthesis of some heterocyclic substituted chromones was undertaken and results were reported depicting the structural elucidation based upon IR, PMR. Results of 13C-NMR spectral studies of few heterocyclic substituted chromones constitute the subject matter of the present communication.